Quercus infectoria gall extracts reduce quorum sensing-controlled virulence factors production and biofilm formation in Pseudomonas aeruginosa recovered from burn wounds - Akhter Ahmed Ahmed; Fraidoon Abdulqadir Salih (BMC, 2019)
Abstract Background Quercus gall extracts' ability to kill pathogens in vitro and even removal of chronic drug-resistant infections has been reported by several studies. The current investigation is focused on the action of extracts of Quercus infectoria gall in their sub-inhibitory concentrations on the corresponding bacterial behaviours instead of killing them. Methods The effect of gall extracts on the quorum sensing (QS) associated virulence of multiple drug resistant Pseudomonas aeruginosa recovered from burns wounds was studied. The influence of different extracts on the production of bacterial virulence and biofilm, and expression of the genes encoding quorum sensing and exotoxin A were investigated. Quorum sensing is a crucial regulator of virulence and biofilm development in Pseudomonas aeruginosa and other medical related microbes. Results Experiments to characterise and quantify Q. infectoria gall extracts impact on the quorum sensing networks of P.aeruginosa revealed that the expression of las, rhl, and exotoxin A (ETA) genes levels including the associated virulence were reduced by the extracts at their subinhibitory concentrations. Conclusions The obtained results indicated that extracts of Q. infectoria galls fight infections either by their inhibitory constituents, which vigorously eradicate cells or by disruption of the pathogens quorum sensing system through weakening the virulence and bacterial coordination.